A precursor‐inducible zebrafish model of acute protoporphyria with hepatic protein aggregation and multiorganelle stress. Issue 5 (2nd February 2016) - Elenbaas, Jared S.; Maitra, Dhiman; Liu, Yang; Lentz, Stephen I.; Nelson, Bradley; Hoenerhoff, Mark J.; Shavit, Jordan A.; Omary, M. Bishr
Abstract : Protoporphyria is a metabolic disease that causes excess production of protoporphyrin IX (PP‐IX), the final biosynthetic precursor to heme. Hepatic PP‐IX accumulation may lead to end‐stage liver disease. We tested the hypothesis that systemic administration of porphyrin precursors to zebrafish larvae results in protoporphyrin accumulation and a reproducible nongenetic porphyria model. Retro‐orbital infusion of PP‐IX or the iron chelator deferoxamine mesylate (DFO), with the first committed heme precursor α‐aminolevulinic acid (ALA), generates high levels of PP‐IX in zebrafish larvae. Exogenously infused or endogenously produced PP‐IX accumulates preferentially in the liver of zebrafish larvae and peaks 1 to 3 d after infusion. Similar to patients with protoporphyria, PP‐IX is excreted through the biliary system. Porphyrin accumulation in zebrafish liver causes multiorganelle protein aggregation as determined by mass spectrometry and immunoblotting. Endoplasmic reticulum stress and induction of autophagy were noted in zebrafish larvae and corroborated in 2 mouse models of protoporphyria. Furthermore, electron microscopy of zebrafish livers from larvae administered ALA + DFO showed hepatocyte autophagosomes, nuclear membrane ruffling, and porphyrin‐containing vacuoles with endoplasmic reticulum distortion. In conclusion, systemic administration of the heme precursors PP‐IX or ALA+DFO into zebrafish larvae provides a new model of acute protoporphyria with consequent hepatocyte protein aggregation and proteotoxic multiorganelle alterations and stress.—Elenbaas, J. S., Maitra, D., Liu, Y., Lentz, S. I., Nelson, B., Hoenerhoff, M. J., Shavit, J. A., Omary, M. B. A precursor‐inducible zebrafish model of acute protoporphyria with hepatic protein aggregation and multiorganelle stress. FASEB J. 30, 1798–1810 (2016). www.fasebj.org